Where did Braverman go wrong?: a marxist response to the politicist critiques - Sartelli, Héctor Eduardo (2014)
Braverman is considered an unquestionable reference of Marxist labour process. The objective of this paper is to show that despite Braverman's undeniable achievements he forsakes the classical Marxist notions related to work organization, i. e. simple cooperation, manufacture and large-scale industry and replaces them with the notion of Taylorism. We also intend to show that because of this abandonment, Braverman cannot explain properly how the deskilling tendency operates in different historical periods, and in distinct industry branches. Finally, we try to demonstrate that those Marxist concepts neglected by Braverman are especially useful to understand labor unrest related to job organization. Braverman overvalues the incidence of labor fragmentation and direct forms of control and disregards the impact of mechanization achieved with the emergence of Large-scale industry and the new forms of control associated with it. Whereas Braverman?s allegedly Marxist orthodoxy is considered responsible for this, in fact, exactly the opposite can be asserted: the weaknesses of the otherwise noteworthy work of Harry Braverman are grounded in his relinquishment of some crucial Marxist concepts. We state that labor processes conventionally considered Taylorist or Fordist can be reconceptualized in Marxist classic terms allowing a better understanding of the dynamic of conflicts regarding labor process.